Open Fault Diagnosis and Tolerance Control for Grid-Connected Hybrid Active Neutral-Point-Clamped Inverters with Optimized Carrier-Based Pulse Width Modulation - Kim, Ye Ji; Kim, Sang Hun; Kim, Seok Min; Lee, Kyo Beum (IEEE Access, 2020)
This paper proposes open fault diagnosis and tolerance control methods for grid-connected hybrid active neutral-point-clamped (ANPC) inverters with optimized carrier-based pulse width modulation. The hybrid ANPC inverter is composed of silicon carbide metal-oxide-semiconductor field effect transistors and Si-insulated gate bipolar transistors. Open faults of switch devices lead to the distortion of output currents, inverter performance degradation, and low reliability. Therefore, the open-circuit fault diagnosis and the tolerance control methods should be handled to improve the reliability of the inverter. The fault tolerance control methods for grid-connected inverters should also consider the fixed voltage modulation index as the modulation index is fixed. In this study, the proposed fault tolerance control method handles the open fault without reducing the modulation index. The implementation of the proposed method is easy and can be conducted through a simple change in the reference waveform. The effectiveness of the proposed fault detection and fault tolerance control methods was verified through the simulation and experimental results.
Keywords: Active neutral point clamped; Fault tolerance control; Grid connected inverters; Grid-connected; Open circuit faults; Output current; Performance degradation; Tolerance control; Active neutral-point clamped; fault diagnosis; fault tolerance control; grid-connected; open fault; reliability; silicon carbide